Current Honey Market in India - Volume and Value - Ramashrit Singh, (International Journal of Ayurveda and Pharma Research, 2021)
Honey is known for its dietary as well as medicinal uses in India. India was leading the global honey business till the colonial rule took over the honey into its hands. The beehives were traditionally harvested till 19th century and Europeans as well as British introduced beekeeping in India. Since then, beekeeping has become another way of livelihood for the rural communities and tribes. However, the activity remains unorganized for various reasons including logistics and migration. Gradually, National Bee Board was established and recently National Beekeeping and Honey Mission is launched. It is estimated that more than 5 lakh farmers / beekeepers are associated with the honey production in this country. The data on the volume and value of honey is still missing therefore an attempt has been made in this paper by using the top to bottom approach. This data would help the traders as well as the government to focus on the financials of honey trade.